Faktor Kinerja UMKM: Analisis Efek Mediasi Dukungan Pemerintah - Adillah, Egga; Aditya, Friska; Setiawan, Aris (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a crucial impact on the economic progress of numerous nations, particularly in developing regions. Acting as the cornerstone of the local economy, MSMEs are vital in propelling economic advancement. They make substantial contributions to job creation, revenue generation, and the overall economic progress. Nonetheless, despite their significance, MSMEs frequently encounter a range of obstacles that impact their financial viability and ongoing survival. This study delves into an in-depth examination of how the financial performance of MSMEs can be enhanced through Financial Digitalisation, Financial Inclusion, and Access to Capital, with a particular focus on the pivotal role of government support as a strengthening factor in this relationship. The research methodology employed in this investigation is quantitative, employing a sample of MSMEs located in Pontianak City. Data analysis was conducted using the Structural Equation Model (SEM) and tested with the Smart PLS statistical tool. The findings suggest that financial digitalisation and access to capital positively influence the performance of MSMEs, with government support acting as a mediator. However, government support is not able to mediate the impact between Financial Inclusion and MSME performance.